Review: Sintesis Dan Karakterisasi Nanopartikel Emas (AuNP) Serta Konjugasi AuNP Dengan DNA Dalam Aplikasi Biosensor Elektrokimia - Egista Istioka Fazrin; Annisa Ilma Naviardianti; Santhy Wyantuti; Shabarni Gaffar; Yeni Wahyuni Hartati (University of Bengkulu, 2020)
The use of gold nanoparticles (AuNP) is an appropriate one in the development of biosensors because it has a unique, strong adsorption, high biocompatibility, and large surface area. AuNPs can be synthesized by various methods with the same synthesis principle by reducing Au3+ to Au. This review explains the various methods of AuNP synthesis and their characteristics, the interaction of AuNP with biomolecules including DNA, and the application of AuNP-DNA bioconjugates in biosensors. Several applications of AuNP-DNA bioconjugates as electrochemical biosensors in the past two years are proposed in this review.